Health Belief Model–Based Health Education and Maternal Health Behaviors During Pregnancy: A Literature Review: A LITERATURE REVIEW - Francisca de Jesus Liberato; Sri Wahyuni; Muh. Abdurrouf; Herry Susanto (Indonesian Journal of Global Health Research, 2026)
Maternal health behaviors are a critical determinant of successful maternal healthcare outcomes; however, adherence to recommended health behaviors during pregnancy remains a significant challenge. Health education based on the Health Belief Model (HBM) has been recognized as an effective approach for modifying health behaviors by addressing individual perceptions and motivational factors. This literature review aimed to synthesize empirical evidence on the effectiveness of Health Belief Model–based health education in improving maternal health behaviors during pregnancy. This study employed a systematic literature review in accordance with the PRISMA 2020 guidelines. Articles were retrieved from PubMed, ScienceDirect, Google Scholar, and national journal databases, covering publications from 2020 to 2025. A comprehensive literature search was conducted using predefined keywords, including Health Belief Model, Health Behaviors During Pregnancy, Health Education, and Pregnant Women. A total of 312 articles were identified, of which 72 duplicates were removed. The remaining 240 articles were screened based on titles and abstracts, resulting in the exclusion of 205 articles. Subsequently, 35 full-text articles were assessed for eligibility. Based on predefined inclusion and exclusion criteria, 10 open-access studies involving pregnant women, applying the Health Belief Model, and reporting maternal health behavior outcomes were included in the qualitative synthesis. Health Belief Model–based health education was found to significantly improve maternal health behaviors, including adherence to antenatal care (ANC) visits, nutritional practices, compliance with iron–folic acid supplementation, physical activity, and disease prevention behaviors. Health education grounded in the Health Belief Model is an effective and relevant approach for enhancing maternal health behaviors during pregnancy and warrants integration into evidence-based maternal healthcare services.